Effect of probenecid on the pharmacokinetics of DTIC-14C - Chen, Tai Wai David 1951-
The effects of probenecid on the pharmacokinetics of DTIC were studied in six New Zealand Albino rabbits by radioisotope methodology. Two treatments were given to the six animals: one treatment consisted of DTIC alone, and the other treatment consisted of probenecid followed by DTIC. A dose of 150 mg/kg of body weight of probenecid was administered orally to the animals and a dose of 10 mg of radioactive DTIC was injected intravenously to each animal. Plasma samples were obtained at regular intervals and were analyzed by liquid scintillation counting techniques. The data were computer analyzed and the results were reported in tabular form.